KONTROVERSI KESAKSIAN PEREMPUAN DALAM QS AL-BAQARAH (2): 282 ANTARA MAKNA NORMATIF DAN SUBSTANTIF DENGAN PENDEKATAN HUKUM ISLAM - Asriaty Asriaty (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2016)
Focus discussion of this article is debate concerning female testimony in relation to universal and comprehensive understanding including female position during the time of Revelation. Al-Baqarah: 282 has given a recognition for female as a witness before the law as a new improvement denied by jahiliyah. This verse acknowledges women as an autonomous legal subject. There is a humanity spirit of this verse. Thus, this verse should not be understood literally-scripturally. Rather, it necessitates contextual understanding based on the past and present situation and also differentiates between the core of religious teaching and that of dynamic one.